Tandem Use of Multiple Tracers and Metrics to Identify Dynamic and Slow Hydrological Flowpaths - Dwivedi, Ravindra; Eastoe, Christopher; Knowles, John F.; McIntosh, Jennifer; Meixner, Thomas; Ferre, Paul A. Ty; Minor, Rebecca; Barron-Gafford, Greg; Abramson, Nathan; Stanley, Michael; Chorover, Jon (Frontiers in Water, 2022)
Current understanding of the dynamic and slow flow paths that support streamflow in mountain headwater catchments is inhibited by the lack of long-term hydrogeochemical data and the frequent use of short residence time age tracers. To address this, the current study combined the traditional mean transit time and the state-of-the-art fraction of young water (Fyw) metrics with stable water isotopes and tritium tracers to characterize the dynamic and slow flow paths at Marshall Gulch, a sub-humid headwater catchment in the Santa Catalina Mountains, Arizona, USA. The results show that Fyw varied significantly with period when using sinusoidal curve fitting methods (e.g., iteratively re-weighted least squares or IRLS), but not when using the transit time distribution (TTD)-based method. Therefore, Fyw estimates from TTD-based methods may be particularly useful for intercomparison of dynamic flow behavior between catchments. However, the utility of 3H to determine Fyw in deeper groundwater was limited due to both data quality and inconsistent seasonal cyclicity of the precipitation 3H time series data. Although a Gamma-type TTD was appropriate to characterize deep groundwater, there were large uncertainties in the estimated Gamma TTD shape parameter arising from the short record length of 3H in deep groundwater. This work demonstrates how co-application of multiple metrics and tracers can yield a more complete understanding of the dynamic and slow flow paths and observable deep groundwater storage volumes that contribute to streamflow in mountain headwater catchments.